PERSENTASE LEMAK PADA ORGAN HATI TIKUS JANTAN (Sprague Dawley) OBES YANG DIBERI TEPUNG BUAH NAGA MERAH (Hylocereus polyrhizus) DAN OLAHRAGA RENANG - Maigoda, Tonny Cortis; Sulaeman, Ahmad; Setiawan, Budi (Jurnal Gizi dan Pangan, 2016)
The purpose of this study was to determine the effects of red dragon fruit (Hylocereus polyrhizus) powder and swimming exercise on fat distribution in the liver organ of white male rats model with obesity. The design of this study was experimental study with randomly factorial design. There were 24 rats divided into two groups, 20 rats were induced to be obese by giving high fat diet, and 4 rats were given standard diet. For intervention period (4 weeks) 20 obese rats were divided into 5 groups namely (1) standard diet (SD), (2) high fat diet (HFD), (3) high fat diet plus swimming exercise (HFD+SE), (4) high fat diet plus red dragon fruit powder (HFD+RDFP), and (5) high fat diet plus red dragon fruit powder plus swimming exercise (HFD+RDFP+SE). Research results showed that fat distribution and visceral fat weight were different significantly among intervention groups (p<0.05). The lowest percentage of fat distribution was occured in RDFP+HFD+SE group (21.44%) and the lightest weight of central fat was also occurred in the same group (7.73 g). This study showed that in four weeks intervention, red dragon fruit powder and swimming exercise had a relatively similar clinical effects on reducing percentage of fat in the liver and visceral fat weight.